Fast gas chromatography-atmospheric pressure (photo)ionization mass spectrometry of polybrominated diphenylether flame retardants - Di Lorenzo, Robert A. (Anal Chim Acta, 2019)
Gas chromatography (GC) and mass spectrometry (MS) are powerful, complementary techniques for the analysis of environmental toxicants. Currently, most GC-MS instruments employ electron ionization under vacuum, but the concept of coupling GC to atmospheric pressure ionization (API) is attracting revitalized interest. API conditions are inherently compatible with a wide range of ionization techniques as well high carrier gas flows that enable fast GC separations. This study reports on the application of atmospheric pressure chemical ionization (APCI) and a custom-built photoionization (APPI) source for the GC-MS analysis of polybrominated diphenyl ethers (PBDEs), a ubiquitous class of flame retardants. Photoionization of PBDEs resulted in the abundant formation of molecular ions M(•+) with very little fragmentation. Some photo-oxidation was observed, which differentiated critical BDE isomers. Formation of protonated molecules [M+H](+) did not occur in GC-APPI because the ionization energy of H(2)O (clusters) exceeds the energy of the ionizing photons. Avoiding mixed-mode ionization is a major advantage of APPI over APCI, which requires careful control of the source conditions. A fast GC-API-MS method was developed using helium and nitrogen carrier gases that provides good separation of critical isomers (BDE-49/71) and elution of BDE 209 in less than 7 min (with He) and 15 min (with N(2)). It will be shown that the GC-APPI and GC-APCI methods match the sensitivity and improve upon the selectivity and throughput of established methods for the analysis of PBDEs using standard reference materials (NIST SRM 1944 and SRM 2585) and selected environmental samples.